CORPORATE GOVERNANCE MEMODERASI HUBUNGAN ANTARA ASIMETRI INFORMASI DAN KEBIJAKAN DIVIDEN TERHADAP MANAJEMEN LABA - Novita Eka Berlianti (2021)
This quantitative research was conducted to examine the influence of information asymmetry and dividend policy towards earnings management, and how is the role of corporate governance in moderating the relationship between information asymmetry and dividend policy on earnings management. Sample in this research is 46 banking sector companies listed on the Indonesia Stock Exchange for 2015-2019 period and chosen by purposive sampling method. The final sample used in this research is 9 banking companies. Data analysis method used in this research is Multiple Linear Regression Analysis with Eviews 9 and significance level of 5%. The results of the testing showed that: (1) Information asymmetry has no significance influence on earnings management; (2) Dividend policy has negative significance influence on earnings management; (3) Corporate governance cannot moderates the relationship between information asymmetry on earnings management; (4) Corporate governance cannot moderates the relationship between dividend policy on earnings management.